Use of technological strategies as an educational policy of continuity in the university academic processUso de estrategias tecnológicas como política educativa de continuidad en el proceso académico universitario. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is a need to know the basis of the use of technological strategies and to apply them in a particular case in the teaching of Mathematics; therefore, the general objective of the research is to explain the importance of the use of technological strategies as an educational policy of continuity in the university academic process. The study is based on the historical hermeneutic paradigm of mixed approach. The method used was logical inductive, and the research is explanatory. A careful tracking of documentary information was carried out in which the use of technological strategies as an educational policy of continuity is addressed. On the other hand, it had a pre-experimental design in the achievement of Mathematics skills using technological strategies, such as video tutorials. The fundamentals of the use of technological strategies are investigated, analyzing the use and benefits presented in the virtual modality in university education in the area of Mathematics. The results indicate that the use of technological strategies should be considered as an educational policy of continuity in the university educational process, since they contribute to the development and continuous improvement of education in the area of Mathematics in the country. The results also indicate that the evaluation of the contents of Mathematics and the opinion of the teachers were favorable to the use of the technological strategy in their teaching practice in the reality of the Pandemic COVID-19. The conclusions obtained report high predisposition of the participants to the use of the digital technological strategy, a high percentage of very favorable opinion of the teachers who conducted the subject of Mathematics through the use of appropriate technological strategies and this corroborates the foundations exposed by various authors consulted.